The politics of adaptive climate management: Scientific recipes and lived reality. (28th February 2018) - Warner, Jeroen F.; Wesselink, Anna J.; Geldof, Govert D.
Abstract : While excited about the ground‐breaking work coming out of the epistemic community promoting adaptive (climate) management (AM), we worry about its tendency to ignore normative implications originating in the implicit worldviews underlying AM literature. Generally, AM has a "green" ideology and focuses on the bioregion as the only sensible level for analysis and action. This tendency for systemic functionalism of AM‐as‐(green)‐policy‐prescription depoliticizes an issue ("what to do about climate change") that is political through and through. For example, those who stand to lose their livelihood as a result of AM plans or simply cannot adapt so fast may resist AM propositions. Implementing AM in practice thereby often leads to social and institutional engineering to overcome resistance. AM in academia seems quite far removed from the "real worlds" of social deliberation and praxis where policy is made and implemented, and where other values and interests than those implicit in AM prevail. We therefore highlight the importance of practices on the ground, claiming AM is not achieved by bioregional policies, but developed "on the hoof" at locally appropriate scales. Everyday professional work is characterized by "organized improvisation" where tacit professional and experiential knowledge are of prime importance. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Abstract : From scientific recipes to lived reality.